Versatile and easy-to-assemble measurement system for impedance-based structural health monitoring - Baptista, F. G. [UNESP]; Vieira Filho, Jozué [UNESP]; Oki, N. [UNESP]; Turra, A. E. [UNESP]; Lopes, V. [UNESP]; Inman, D. J. (My University, 2011)
In this paper we present a versatile and easy-to-assemble measurement system for structural health monitoring (SHM) based on the electromechanical impedance (EMI) technique. The hardware of the proposed system consists only of a common data acquisition (DAQ) device with external resistors and allows real-time data acquisition from multiple sensors. Besides the low-cost compared to conventional impedance analyzers, the hardware and the software are simple and easier to implement than other measurement systems that have been recently proposed.
Keywords: Electromechanical impedance techniques; External resistors; Impedance analyzer; Measurement system; Multiple sensors; Real-time data acquisition; Data acquisition; Hardware; Intelligent structures; Maintenance; Measurements